Molecular Epidemiology of Streptococcus uberis Isolates from Dairy Cows with Mastitis - Phuektes, Patchara (American Society for Microbiology, 2001)
Pulsed-field gel electrophoresis and antimicrobial sensitivity testing were used as tools to investigate the epidemiology of Streptococcus uberis mastitis in dairy cows. A total of 62 different strains were found among 138 isolates from the four herds investigated, and between 10 and 26 different strains were found in each herd. There was no strain common to all four herds. Identical strains of S. uberis were detected from different quarters of individual cows and from cows within the same herd, suggesting that transmission from quarter to quarter and cow to cow had occurred. Despite the great variation in S. uberis strains, persistent infection with the same strain within a lactation was observed in most cows. Predominant strains were present in two herds. Preliminary investigations could not clarify why these particular strains might predominate, but in one herd there was a significant difference between the prevalence of clinical mastitis in quarters infected with the predominant strain and that in quarters infected with other strains, suggesting the greater virulence of the predominant strain. The wide variety of S. uberis strains found is consistent with an environmental source of S. uberis. However, evidence of direct transmission, the persistence of infection, and the predominance of particular strains in some herds indicate that S. uberis infections are epidemiologically complex and that the relative importance of these factors in the occurrence of mastitis may differ between herds.